Peer Research in a Multi-National Project With Migrant Youth: Re-Thinking Vulnerability and Participatory Approaches - Amalia Gilodi; Louise Ryan; Zeynep Aydar (Forum: Qualitative Social Research)
Adopting a critically reflexive approach, we contribute to discussions on how participatory approaches, and peer research specifically, can be implemented, problematising the boundaries, opportunities and implication of the participation of young people from marginalised groups in research projects. We achieve this goal through three consecutive steps. First, we present the peer research approach in theory. Here, drawing on the wider literature, we critically engage with concepts of vulnerability, positionality and questions of inclusive participation and empowerment. Second, presenting concrete examples and lessons learned from our experiences with a multi-national project, we consider the practical obstacles, critical considerations, and advantageous outcomes associated with the inclusion of young migrants as peer researchers in this large European project. Third, we examine the accounts of a group of peer researchers to critically reflect on what characterises their participatory experiences and their impact, adopting the notion of vulnerability reconceptualised as an analytical lens. In the conclusion, we summarise key insights presented in our paper and offer some final reflections.